External Morphology of Neophilaenus lineatus(Linnaeus 1758) (Homoptera: Cercopidae) in Iraq New Record Species - S. AL-Asady, Hassan; T. AL-Hasanawy, Hala (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The work included external morphological study of the frog hopperNeophilaenuslineatus(Linnaeus), 1758 which belongs to the family Cercopidae of order Homoptera. The studied species is regarded as new record to Iraqi funa. The study involved with the most important toxonomic external characters such as the head, thorax, abdomen and some of their appendages in addition to male and female genitalia